Development of a RACE-based RNA-Seq approach to characterize the T-cell receptor repertoire of porcine γδ T cells. (April 2020) - Hammer, Sabine E.; Leopold, Melanie; Prawits, Lisa-Maria; Mair, Kerstin H.; Schwartz, John C.; Hammond, John A.; Ravens, Sarina; Gerner, Wilhelm; Saalmüller, Armin
Abstract: Recent data suggest that porcine γδ T cells exhibit a similar degree of functional plasticity as human and murine γδ T cells. Due to the high frequency of TCR-γδ + cells in blood and secondary lymphatic organs, the pig is an attractive model to study these cells, especially their combined features of the innate and the adaptive immune system. Using a 5' RACE-like approach, we translated a human/murine NGS library preparation strategy to capture full-length V-(D)-J TRG and TRD clonotypes in swine. After oligo(dT) primed conversion of input RNA, the cDNA population was enriched for full-length V(D)J TCR transcripts with porcine-specific primers including Illumina adaptor sequences as overhangs for Illumina MiSeq analysis. After quality control and processing by FastQC and ea-utils, porcine TRG and TRD sequences were mapped against the human IMGT reference directory. Porcine blood-derived CD2 + and CD2‾ TCR-γδ + cells exhibited two distinct clonotypes Vγ11JγP1 (74.6%) and Vγ10JγP1 (57.7%), respectively. Despite the high TCR-δ diversity among CD2 + cells (39 clonotypes), both subsets shared the same abundant Vδ1DδxJδ4 clonotype at approximately identically frequencies (CD2 + : 31.2%; CD2‾: 37.0%). The flexible nature of this approach will facilitate the assessment of organ-specific phenotypes of γδ T cell subsets alongside with their respective TCR diversity at single cell resolution. Graphical abstract: Image 1 Highlights: Establishment of a NGS-based strategy for γ/δ TCR profiling of porcine γδ T cells. Porcine blood-derived CD2 + TCR-γδ + cells showed a high TCR-δ diversity (39 clonotypes). Both subsets shared the abundant Vδ1DδxJδ4 clonotype (CD2 + : 31.2%; CD2 - : 37.0%). The most abundant TRG clonotype in CD2 + TCR-γδ + cells was Vγ11JγP1 (74.6%). In CD2 − TCR-γδ + cells, the clonotype Vγ10JγP1 occurred at highest frequency (57.7%).